2014
DOI: 10.1007/978-1-4614-3209-8_60
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapeutic Strategies for P23H RHO-Linked RP

Abstract: The first autosomal dominant mutation identified to cause retinitis pigmentosa in the North American population was the substitution of proline to histidine at position 23 of the rhodopsin gene (P23H RHO). Many biochemical studies have demonstrated that P23H mutation induces rhodopsin (RHO) misfolding leading to endoplasmic reticulum stress. Herein, we review current thinking of this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We have recently shown that reductions in rod gene expression caused by treatment with PR1 were sufficient to slow the degeneration of Rho P23H photoreceptors in vitro ( Nakamura et al, 2016 ). The Rho P23H mutation causes misfolding of Rhodopsin in rod photoreceptors, which leads to activation of the unfolded protein response and eventually results in rod and cone death ( Nguyen et al, 2014 ). In Rho P23H mice, most rod photoreceptors undergo apoptosis by the end of the third postnatal week ( Sakami et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that reductions in rod gene expression caused by treatment with PR1 were sufficient to slow the degeneration of Rho P23H photoreceptors in vitro ( Nakamura et al, 2016 ). The Rho P23H mutation causes misfolding of Rhodopsin in rod photoreceptors, which leads to activation of the unfolded protein response and eventually results in rod and cone death ( Nguyen et al, 2014 ). In Rho P23H mice, most rod photoreceptors undergo apoptosis by the end of the third postnatal week ( Sakami et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, when abnormalities exceed the homeostatic capacity of the UPR, cell death signaling molecules such as the CCAAT-enhancer-binding protein (C/EBP) homologous protein (CHOP) are induced to promote the transcription of pro-apoptotic molecules. Therefore, ER stress can be involved in cell death, and the pathogenesis of blindness due to retinitis pigmentosa, an inherited retinal degeneration, at least partly involves ER stress [1921]. Light exposure-induced ER stress was previously reported in a photoreceptor cell line [22, 23] and in the retinal pigment epithelium (RPE), which maintains photoreceptors, of autophagy-deficient mice [24, 25], and in the neural retina [23].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 – 3 ] In particular, the P23H mutation of rhodopsin is the most common cause of autosomal dominant retinitis pigmentosa (ADRP) in North America, as it is responsible for 12% of all known cases. [ 3 5 ] In this form of RP, the mutant rhodopsin is misfolded, which may lead to endoplasmic reticulum stress and, ultimately, rod cell death (for review see [ 6 ]). However, in P23H knock-in mice, the IRE1 pathway and not the pro-apoptotic PERK pathway is activated.…”
Section: Introductionmentioning
confidence: 99%